1984
DOI: 10.1007/bf00313932
|View full text |Cite
|
Sign up to set email alerts
|

Adrenoleukodystrophy: a clinical variant presenting as olivopontocerebellar atrophy

Abstract: A case of adrenoleukodystrophy showing neurological features of olivopontocerebellar atrophy is described. A CT scan demonstrated marked atrophy in both cerebellum and pons. ACTH stimulation produced no rise in the plasma cortisol level but a significant rise in the plasma aldosterone level. The ratios of C26:0 to C22:0 in fatty acids of sphingomyelin from erythrocyte membrane and plasma were increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…The relative frequency of the adult cerebral form is calculated to be about one third of total patients, which is higher than the childhood form. This study also clarified that OPC is frequent in Japan: most of the previous reports on OPC have been from Japan (Ohno et al 1984;Moser et al 2001).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The relative frequency of the adult cerebral form is calculated to be about one third of total patients, which is higher than the childhood form. This study also clarified that OPC is frequent in Japan: most of the previous reports on OPC have been from Japan (Ohno et al 1984;Moser et al 2001).…”
Section: Discussionsupporting
confidence: 71%
“…The adult cerebral form, characterized by dementia or psychological problems, was the third most common form and its incidence was higher in the 1990s than in the 1980s. The olivo-ponto-cerebellar form (OPC) (Ohno et al 1984), characterized by gait disturbance and ataxia, composed 8.4% of total patients. The number of presymptomatic boys with no clinical manifestations and symptomatic girls was small, and no patient with isolated insufficiency of the adrenal gland (Addison's disease phenotype) was reported.…”
Section: Resultsmentioning
confidence: 99%
“…Kuroda et al [ 11 ] described a 28-year-old man with cerebellar signs and hyperreflexia; in the adrenal gland the presence of trilamellar structures was confirmed by electron microscopy. In 1983, Ohno et al [21] reported the case of a 54-yearold man with cerebellar signs but without spasticity, in whom the diagnosis had been made following analysis of plasma very-long-chain fatty acid. As previously mentioned, in 3 cases of the present kindred, neurological symptoms were apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 1% of patients have unusual forms that are not encompassed in this classification. These include patients with predomi nantly cerebellar involvement [24] and 2 patients in our series who had psychomotor retardation, possibly unre lated, since birth. Figure 1 shows the age of onset of neurological symp toms in the various ALD phenotypes.…”
Section: The Six Main Phenotypes Among Ald Hem ¡Zygotes and Their Relmentioning
confidence: 99%